2020
DOI: 10.35609/jmmr.2020.5.1(5)
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model of Market Orientation on Innovation Performance

Abstract: Objective –This paper seeks to provide new insights into the relationship between market orientation and innovation performance by empirically testing the direct effect of market orientation (MO) on innovation performance and exploring the effects of moderation in marketing constructs, namely customer relationship management (CRM) and knowledge management, in these relationships. Methodology/Technique – This study adopts a cross-sectional research design. Data is collected from export-oriented manufacturing sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 49 publications
(119 reference statements)
2
12
0
Order By: Relevance
“…Moreover, the results revealed that CDMO is positively related to CS. The research findings are also supported by previous studies (e.g., Deshpande et al, 1993; Khan & Ghouri, 2018; Najafi-Tavani et al, 2016; Wahyuni & Astawa, 2020; Wang, Ling et al, 2021), in which it is suggested that CO, COM, IFC are significantly related to superior business performance. These findings inferred that restaurants could increase CS by improving customer value using the components of MO, that is, CO, competitive fairness, and functional demands of the customers (Crick, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the results revealed that CDMO is positively related to CS. The research findings are also supported by previous studies (e.g., Deshpande et al, 1993; Khan & Ghouri, 2018; Najafi-Tavani et al, 2016; Wahyuni & Astawa, 2020; Wang, Ling et al, 2021), in which it is suggested that CO, COM, IFC are significantly related to superior business performance. These findings inferred that restaurants could increase CS by improving customer value using the components of MO, that is, CO, competitive fairness, and functional demands of the customers (Crick, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…MO represents the organization's culture by concentrating on providing better competitive value to consumers as well as identifying trends in target markets to fulfill consumers' increasing demands (Akroush & Mahadin, 2019). MO is considered a distinct process that focuses on CS and is positioned as an organizational culture in the central business operation (Roach et al, 2014), thereby creating superior customer value and improving business performance (Kohli & Jaworski, 1990;Wahyuni & Astawa, 2020). Singh and Ranchhod (2004) suggest organizations should not only be customer-oriented but also have information about competitors to meet customer expectations.…”
Section: Customer-defined Market Orientation and Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzed by categories of professional situations, most of the distributions are not expected in all cases. Spearman's and Pearson's correlations, means, and standard deviations, as well as the parameters of the Kruskal-Wallis test and ANOVA test, are shown in Table 6 [85].…”
Section: Category Samplesmentioning
confidence: 99%
“…When analyzed by categories of professional situations, most of the distributions are not expected in all cases. Spearman's and Pearson's correlations, means, and standard deviations, as well as the parameters of the Kruskal-Wallis test and ANOVA test, are shown in Table 6 [85]. Regarding the correlations:…”
Section: Category Samplesmentioning
confidence: 99%